2015
DOI: 10.1039/c5ra01395j
|View full text |Cite
|
Sign up to set email alerts
|

Xylene gas sensor based on Ni doped TiO2 bowl-like submicron particles with enhanced sensing performance

Abstract: Bowl-like TiO2 submicron particles prepared by electrospray technique were used to detect xylene gas and Ni element was added into TiO2 to improve the gas sensing performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 26 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Hence, we studied the effects of calcination on gas sensing properties of WO 3 lamellae. [38][39][40] The recovery time (s rec ) exposures to 100 ppm xylene were about 24 s, 18 s, 17 s, 15 s for WO 3 annealed at 300 C 400 C, 500 C, 600 C. The response time of the sensors is obviously shorter than the recovery time, which indicates that the adsorption of xylene gas and its subsequent reduction are generally shorter than desorption and diffusion of the product gases. 6 shows the response of WO 3 nanolamella gas sensors annealed at different temperatures to 100 ppm xylene at different operating temperatures.…”
Section: Gas-sensing Propertiesmentioning
confidence: 97%
“…Hence, we studied the effects of calcination on gas sensing properties of WO 3 lamellae. [38][39][40] The recovery time (s rec ) exposures to 100 ppm xylene were about 24 s, 18 s, 17 s, 15 s for WO 3 annealed at 300 C 400 C, 500 C, 600 C. The response time of the sensors is obviously shorter than the recovery time, which indicates that the adsorption of xylene gas and its subsequent reduction are generally shorter than desorption and diffusion of the product gases. 6 shows the response of WO 3 nanolamella gas sensors annealed at different temperatures to 100 ppm xylene at different operating temperatures.…”
Section: Gas-sensing Propertiesmentioning
confidence: 97%
“…Therefore, anatase TiO 2 seems to be the less suitable candidate for wide use as a high-temperature H 2 sensor. Previous studies have reported that this disadvantage can be overcome by suitably doping the TiO 2 [ 21 , 22 , 23 , 24 , 25 , 26 ]. Another main drawback of a resistive semiconductor metal oxide-based sensor such as TiO 2 is selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that doping is an effective way to improve the gas-sensing properties of sensors based on metal oxide semiconductors. Several works report the effect of Ni doping on TiO 2 sensing properties at low temperatures (<350 °C) [ 22 , 25 , 33 ]. In fact, substituting Ti by Ni, depending on the synthesis method, could change the conductivity type, inducing effective reduction in the bandgap of anatase titanium dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the detection and measurement of xylene are important. Hitherto, various methods, such as gas chromatography, optical waveguides, optical planar Bragg grating sensors, chemical sensors, biosensors, and magneto‐elastic sensors, have been used to detect xylene. Chemical sensors based on metal oxide semiconductors are particularly appealing because of their excellent sensing performance, ease of fabrication, simple operation, low production costs, portability, and miniaturization.…”
Section: Introductionmentioning
confidence: 99%